Russia at War with the West – Still Cold or Already Hot? - Marek Czajkowski (Politeja)
This article aims to determine whether Russo-Western relations can be framed as a war and, consequently, if the concept of a ‘cold war’ could serve as a viable framework for further analysis. It will first briefly revisit the original Cold War and its defining traits. Secondly, the current general aims and goals of both Russia and the West will be described, with particular attention to the security environment and perceptions of national security. This approach will allow for a thorough examination of the main characteristics of the new Cold War. Finally, we will contextualise the war in Ukraine within a ‘cold war’ framework to illustrate how it works.